Pentecostalism and Witchcraft Spiritual Warfare in Africa and Melanesia - Rio, Knut; MacCarthy, Michelle; Blanes, Ruy (Contemporary Anthropology of Religion, 2017)
charismatic Christianity; Holy Spirit; demonology; evangelism; indigenous Pentecostal movements; ethnography